Intratumoral microbial community profiling identifies clinicomolecular and prognostic subtypes of colorectal cancer liver metastasis - Linhai Yan; Xiaoxia Wei; Fangchao Zhong; Lihua Fu; Haiming Ru; Xianwei Mo; Maosen Huang (npj Precision Oncology)
Abstract Intratumoral microbiota are implicated in colorectal cancer liver metastasis (CRLM), but their relationships with clinical characteristics and prognosis remain to be explored. Using 5R 16S rRNA gene sequencing method, we analyzed the intratumoral microbiota of patients with colorectal cancer with and without liver metastasis. CRLM patients were classified into three intratumoral microbial community subtypes (IMCSs). These included IMCS1 (sugar metabolism-related liver metastasis with T cell activation, moderate proliferation and invasion, and median disease-free survival (mDFS) of 22 months), IMCS2 (protein metabolism-related liver metastasis with natural killer cell activation, high proliferation and invasion, and mDFS of 12 months), and IMCS3 (lipid metabolism-related liver metastasis with a pauci-immune phenotype, the highest level of proliferation and invasion, and mDFS of 10 months). Our study establishes intratumoral microbiome subtypes as a novel risk stratification strategy for CRLM, facilitating microbiota-directed therapeutic strategies with potential survival benefits.